Celiac Disease Diagnosis Without Biopsy: Is a 10× ULN Antitransglutaminase Result Suitable for a Chemiluminescence Method?. Issue 4 (April 2018) - Previtali, Giulia; Licini, Lisa; D'Antiga, Lorenzo; Marseglia, Antonio; Ravasio, Rudi; Nembrini, Francesca; Greco, Salvatore; Sonzogni, Aurelio; Azzarà, Giovanna; Ravelli, Paolo; Alessio, Maria G.
ABSTRACT: Objectives: 2012 European Society of Pediatric Gastroenterology, Hepatology and Nutrition guidelines allow to establish a celiac disease diagnosis without duodenal biopsy in symptomatic pediatric patients with antitissue transglutaminase (anti-tTG) titers >10 times the upper limit of normal. For some years now, new chemiluminescence immunoassays have been made available: it is important to establish the clinical performance of anti-tTG and to determine the cut-off best suited to predict Marsh ≥2 to avoid gastrointestinal endoscopy not only in children, but also in the adult population. Methods: A total of 2565 patients performed duodenal biopsy from July 2012 to September 2016; we selected all the patients who had undergone QUANTA Flash anti-tTG immunoglobulin A (IgA) within −3 months of duodenal biopsy and before the start of gluten-free diet. A total of 827 patients fulfilled the criteria for selection. Results: Using a cut-off of 20 chemiluminescent unit (CU; area under the curve: 0.995), sensitivity, specificity, positive, and negative predictive value were 98.2%, 98.4%, 97.9%, and 98.6%, respectively. For the correlation with Marsh ≥2, in the pediatric population, positive predictive values (PPV) were 92.1%, 99%, and 100% at 200 CU (10×), 560 CU (28×), and 1000 CU (50×), respectively. In the adult population PPV was 94.2%, 98.2%, and 100% at 200 CU (10×), 350 CU (15×), and 400 CU (20×). Conclusions: Sensitivity, specificity, positive, and negative predictive value of QUANTA Flash h-tTG IgA were excellent. The cut-off providing an optimized PPV for histological lesions compatible for celiac disease (Marsh ≥2) for the QUANTA Flash h-tTG IgA is 350 CU (15×) in adult and 560 CU (28×) in children.